Design and experiment of a barrel-shaped aeroponic cultivation system - Qi, Shouhe; Ma, Yunfei; Zhang, Mei; Yin, Baoquan; Xu, Zhenyan; Liu, Shuguang (International Journal of Agricultural and Biological Engineering, 2022)
Theoretically, aeroponic cultivation is easy to make plant roots in a better growth environment. In order to give better play to the theoretical advantages of aeroponic cultivation, further optimize the structure of the aeroponic cultivation system, and make the aeroponic cultivation system more scientific and reasonable, a barrel-shaped aeroponic cultivation system is designed. The aeroponic cultivation system is composed of a monitoring and control system, power equipment, nutrient solution storage, and treatment facility, nutrient solution supply pipelines, aeroponic cultivation barrels, and nutrient solution return pipelines. The cultivation system working principle and its technical requirements were analyzed, and its structure for meeting the requirements of large-scale production was determined. A performance test of the barrel-shaped aeroponic cultivation system using cultivated narrow leaved Chinese chives was conducted. The Chinese chives were cultivated to 6 beds of the cultivation barrel. The system supplied nutrient solution every 30 min for 2 min each time. After 5 weeks growth, the length, leaf width, and single weight of Chinese chive ranged from 293-362 mm, 4.1-6.7 mm, and 3.48-5.47 g, respectively, the average length, leaf width, and single weight of Chinese chive were 327 mm, 5.1 mm, and 4.24 g, respectively, and there were no significant differences in the length, leaf width, and single weight of Chinese chive on 6 beds by One-way ANOVA. The test results showed that all the Chinese chive in each bed of the cultivation barrel grew well and uniform, which indicated that the circulation process of nutrient solution supply and return in the system was normal, the process of nutrient solution atomization in the system was uniform, and the aeroponic cultivation system operated normally and stable and could be applied in production. Keywords: aeroponic cultivation, soilless cultivation, facility agriculture, Chinese chive DOI: 10.25165/j.ijabe.20221504.7508 Citation: Qi S H, Ma Y F, Zhang M, Yin B Q, Xu Z Y, Liu S G. Design and experiment of a barrel-shaped aeroponic cultivation system. Int J Agric & Biol Eng, 2022; 15(4): 90–94.